(untitled) (Journal of Engineering Science, 2023)
The main aim of this study is to conduct an economic analysis and a multi-criteria analysis of electric, diesel, and solar irrigation pumps to find the best irrigation technology. After collecting the necessary data, a cost comparison is made between solar and conventional irrigation technologies. The cost of each technology is then compared using a 25-year lifespan to determine which one will be less expensive. Since there are additional important factors to consider while selecting the optimal technology, a multi-criteria analysis is done too. The cost comparison reveals that, in contrast to the other two, the solar system has higher startup expenditures but lower ongoing operating and maintenance costs. According to the cost analysis of the three technologies, solar technology is significantly less expensive than electric and diesel alternatives. Aside from the cost, electric irrigation technology appears to be a better option than solar and diesel technologies when considering other aspects like farmer satisfaction, necessary installation land, technology accessibility, weather obstruction, etc. Journal of Engineering Science 13(2), 2022, 101-110